Cálculo y diseño de una envasadora de leche. - Campoverde Ruíz, Carlos Eduardo (2004)
The present Investigation, it is projected to cooperate to the industrial technical development of the South sector of this Country, and she goes focused to the implementation of modern technology that the production processes in the nutritious field, specifically Milky he/she needs. In this work it is provided relating studies to the calculation and design of an Tinner of milk, in which was carried out the following thing: First it is presented general aspects for the election of the injector and their operation, it also incorporates the description of important elements of the use of a PLC in the control of the Tinner; Likewise mechanical calculations, influential for the design of a bomb to remove and a tree of levies, subsequently a the design of the profile of the levies by means of the sequential mensuration of angles, radios and the follower's displacement. All these calculations provided us the enough data for the Design of tinner of Milk it Schemes it, present in the Annexes.